Analysis of Parking System Development Using Electronic Parking Terminals (EPT) to Improve Services and Revenue in Jakarta - Hariwibowo, Muhammad; Handayani, Susanty; Handayani, Sri (Dinasti Publisher, 2025)
This study discusses the performance issues of the Electronic Parking Terminal (EPT) under the Parking Management Unit of the DKI Jakarta Provincial Transportation Agency due to its dependence on the French Cale Web Office (CWO) system. Since May 2021, the CWO system has experienced disruptions, leaving the TPE unable to operate online. This has had a significant impact on agency performance, delayed employee salary payments, and decreased parking management revenue. The average contribution of parking taxes to Local Own-Source Revenue (PAD) during 2018–2021 was only 0.99%, and TPE revenue fluctuated during 2016–2023. With the increasing number of vehicles in Jakarta, the development of the TPE system is expected to improve parking services, revenue efficiency, and support transparency and accountability in parking tax management. This study uses a mixed-methods approach, with quantitative analysis using SEM-PLS. The results show that service quality is the most dominant factor in increasing the system's net benefit, followed by information quality and system quality. Users and user satisfaction play a crucial mediating role in the indirect effect on Net Benefit. Dependence on a problematic CWO system negatively impacts TPE efficiency and revenue. Developing a local version of the TPE system is a more efficient and independent strategic step. In addition, the high operating cost-to-revenue ratio indicates the need for improved management efficiency.